A review on “monoclonal antibodies: effective treatment against COVID-19” - Dabhadkar, Meghana M.; Palekar, Samiksha Rohidas; Pawar, Kaustubh Navnath (International Journal Of Community Medicine And Public Health, 2022)
Novel coronavirus disease caused by the SARS-CoV-19 virus enters the host cell through the S-spike protein by binding to ACE-2. In December 2019, an outbreak of coronavirus originated from Wuhan, China and by the end of 2020, it was recorded in almost every part of the world including Italy, Germany, Iran, Spain, and also United states. This led to a Pandemic which was declared by World Health Organization on 11th March 2020. SARS-CoV-19 causes mild to moderate illness which leads to acute respiratory syndrome, by causing infection in the nose, sinuses, or upper throat. It can also affect the upper or lower respiratory tract and has caused millions of cases and deaths. Many diagnostic tests have been authorized by the WHO including Direct and Indirect tests. Due to the increase in the number of covid 19 cases, many medications were introduced as per the demands like anti-malarial drugs, anti-viral drugs, antibiotics, anti-inflammatory drugs, steroids, biological agents, etc. The SARS-CoV-2 has a spike protein on its surface that aids in the virus’s attachment to and entry into human cells. To attach to the protein of SARS-spike-CoV-2 and stop the virus from infecting human cells, many monoclonal antibodies like Casirivimab, imdevimab, Tocilizumab, Sarilumab, Itolizumab, Siltuximab have been created. As monoclonal antibodies prevent viruses from entering cells and continuing to proliferate, as well as lowering viral loads and lowering the frequency of hospital visits, they can be used as an alternative to conventional therapies. Hence monoclonal antibody treatment can be considered an effective alternative treatment for treating SARS-CoV-2.